Equivalent standard axle loads analysis on lithuanian arterial highways - Šukevicius, Š. (Видавництво Національного університету «Львівська політехніка», 2007)
As the flows of vehicles, especially heavy goods vehicles are growing on the roads of Lithuania, the remaining deformations of the pavements are appearing and progressing also cracks originate because of low pavement strength. The biggest loads are caused by heavy goods vehicles, which total number increases 17% annually. This paper presents analysis of the damage caused by transport vehicles axle loads to the asphalt pavement roads. This influence estimated through calculation equivalent standard axle load index.